The Epidemiology of Posttraumatic Epilepsy - Christensen, Jakob (Seminars in Neurology, 2015)
Traumatic brain injury is an important contributor to morbidity and mortality, and results in reduced quality of life and lifespan: An estimated 1.7 million traumatic brain injuries occur annually in the United States alone. Traumatic brain injury carries an increased risk of epilepsy that correlates with the severity of the brain injury. Posttraumatic epilepsy accounts for less than 10% of epilepsy, but traumatic brain injury is one of only a few potentially preventable causes of epilepsy. Despite several well-controlled human studies, there is no current preventive treatment available for humans. Therefore, primary prevention is the only proven way to prevent posttraumatic epilepsy.
Keywords: traumatic brain injury; seizures; epilepsy; posttraumatic; epidemiology